Radiation‐Enhanced AF1q Moves Center Stage as a Key Driver to Favorable Tumor Stage in Rectal Cancer Patients - Elisabeth S. Gruber; Georg Oberhuber; Elisabeth Gurnhofer; Robert Eferl; Gerald Timelthaler; Béla Teleky; D. I. Dietmar Georg; Joachim Widder; William Tse; Lukas Kenner (Cancer Medicine, 2025)
ABSTRACT Background Enhanced protein expression of ALL1‐fused gene from chromosome 1q (AF1Q) after (chemo)radiotherapy has been described in vitro, but is largely understudied in gastrointestinal cancer. We aimed to investigate AF1q expression in rectal cancer (RC) patients treated with short‐term radiation therapy and a possible correlation with markers crucial for RC prognosis. Methods A cohort of 75 RC patients scheduled for surgery was defined and patients with moderately locally advanced tumors (cT3Nx) received preoperative hyperfractionated short‐term radiation therapy (cumulative dose 25 Gy). Immunohistochemical analysis was conducted to assess AF1q, STAT1, IDO1 and other prognostic markers (CD3/CD8—Immunoscore, PD‐L1) and marker correlations were evaluated. Results Irradiated tumors exhibited significantly higher AF1q expression than treatment‐naïve samples (n = 60: AF1q + to AF1q+++ 98.3% (n = 59), AF1q‐ 1.7% (n = 1) vs. n = 15: AF1q + 78.6% (n = 11), AF1q‐ 21.4% (n = 4); p < 0.001). Specifically, irradiated tumors showed high STAT1, but low IDO1 expression compared to treatment‐naïve samples (p = 0.019 and p = 0.015, respectively). Overall, enhanced tumoral AF1q expression was associated with negative lymph node stage (p = 0.012) as well as with diminished expression of STAT1 (rs = −0.468, p = 0.038) and IDO1 (rs = −0.246, p = 0.020). Conclusion AF1q is expressed in RC, especially after short‐term radiation therapy. Here, AF1q may support tumor suppression, possibly through the involvement of the pro‐apoptotic STAT1 axis. Further mechanistic evidence and investigation involving a larger patient cohort are needed to validate a radiation‐induced, AF1q‐driven tumor‐suppressing effect, which may impact RC patient outcomes.